Assessing Fiscal Space : An Update and Stocktaking. (Policy Papers; Policy Paper ;, 2018)
This paper reviews the experience with the fiscal space assessment framework that was piloted during 2017-18. In 2016, staff proposed an operational definition of fiscal space and a new four-stage framework for its assessment. These were discussed informally by the Board in June, and a Board paper 'Assessing Fiscal Space: An Initial Consistent Set of Considerations' incorporating Directors' views was published in December. Fiscal space was narrowly defined as the room for undertaking discretionary fiscal policy relative to existing plans without endangering market access and debt sustainability. The framework was developed in response to the need to provide a more systematic approach to assessing fiscal space in the Fund's surveillance. It was designed as a tool to inform the availability of fiscal space over a 3 to 4 year horizon for discretionary action, as opposed to the optimality of its use. Indeed, it was stressed that the availability of space does not necessarily mean that it should be used or should not be further expanded. The framework was piloted in the Article IV consultations of 34 advanced economies and emerging markets, comprising almost 80 percent of global GDP in PPP terms.